Predição de tetrápodes ameaçados no cerrado baseada na relação espécies-área - ROVIDA, Julio Cola (2011)
The current rate of extinctions observed in the entire planet has its origin in high rates of habitat loss due to human population increase. The species-area relationship may be usefull in predicting extinction threats when combined with this loss. Lists of Cerrado s tetrapods were compiled and using the species-area relationship, we predicted values of species a threat. These values were compared with the IUCN Red List. The predictions of threat in all cases were higher than the Red List, except for endemic mammals that reflect the current threat list, and endemic birds whose predictions are lower than the threat level by IUCN. A large portion of species have populations in decline according to IUCN. Part of these results can be explained by a time-lag in the response time to the degradation itself associated with the gaps of knowledge about the species. The relationship could be used as a preliminary threat assessment, and followed by the aggregation of these red lists in order to increase efficiency in conservation planning. Life history, spatial and environmental heterogeneity data, when aggregated, should increase the prediction s accuracy. Major investments in basic biology are necessary in order to achieve maximum information input about the species to be evaluated.